Peran Supervisi Pendidikan dalam Meningkatkan Kinerja Guru dan Kualitas Pembelajaran - Deky Magay; Yari Dwikurnaningsih; Wahyudi Wahyudi (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2024)
Educational supervision is very important in improving teacher performance and school learning quality. This article discusses the role of educational supervision in theory and practice in encouraging increased teacher professionalism and the quality of education. Through effective supervision, teachers can receive ongoing coaching to improve teaching methods and create a better student learning environment. This research uses a qualitative approach by analyzing models of educational supervision, such as instructional supervision, clinical supervision, and collaborative supervision. The aim is to discuss the role of educational supervision in improving teacher performance and learning quality, as well as implementation strategies in the current educational context. This research method uses a qualitative approach with a literature study method. The research results show that a supervision model based on collaboration and effective communication between school principals, supervisors, and teachers can positively impact improving the quality of learning. Therefore, implementing appropriate supervision is very important in supporting teacher professional development and improving the overall quality of education. Suggestions for increasing the effectiveness of educational supervision are to strengthen training for school principals and supervisors in implementing a more adaptive supervision model based on teacher needs.